PERENCANAAN PENINGKATAN TERMINAL BUS KABUPATEN DEMAK - Siti Nurkhamadah; Wulansari Wulansari; Moga Narayudha; Siti Hardiyati (Jurnal Karya Teknik Sipil, 2013)
Demak currently only have a passenger terminal with type B, namely Bintoro Terminal located at Sultan Fattah Street. Problems that occur in the terminal are because there was no separation between the arrival and departure areas causing the queues of vehicles and internal circulation is not smooth. The purpose of this study was to evaluate the condition of existing terminal based on facilities and performance terminal, the terminal optimization plan, determine alternative location and layout plan of the new terminal and its internal and external circulation terminals, pavement structure inside the terminal, and the budget planning. The method used in this study is to evaluate the condition of the existing terminal, optimizing the existing terminal, and planning a new terminal if the optimization is not possible. The primary data used were technical data and data rate of arrival and departure of vehicles. Primary data are obtained by conducting direct surveys to observe the arrival and departure times at each service line. The results of the evaluation of the existing terminal indicate that the terminal is not feasible as terminal type B both in terms of facilities and the performance of the terminal. It is evident from the facility for the arrival and departure areas are not separate. Waiting place for passengers is also very limited and becomes one with the arrival and departure areas.Besides, the availability of terminal area covering 5829 m2 is very less compared to the standard type B terminal area that has been set by the Department of Transportation, which is area of 3,5 ha. If viewed from service lines performance, there are several lines of service that has the traffic intensity values greater than 1. From the optimization results also showed that with adding lines of service plans are obtained for the traffic intensity value of 1,11. The possible solutions is by planning a new terminal as a replacement existing terminal. Results obtained planning a new terminal locations located in the Village Jogoloyo, District Wonosalam, Demak regency.New terminal layout plan based on the needs of the land at the end of life plan based on growth predictions bus trips for 20 years.The results of the planning layout are the circulation patterns AKDP and AKAP bus, angkot and angkudes and private vehicles (cars and motorcycles). The intersection access to terminal is planned intersection of three of sleeves, type-344. The value of degree of saturation (DS) at the entry and exit terminal amounting 0,566 and 0,704 with each delay amounting 9,297 sec/smp and 10,892 sec/smp. Terminal access road is a ring road Demak (4/2D) under DS at the end of life plan is at 1,14, so it takes effort to improve the type of road being 6/2D and obtained values of DS at 0,76.Pavement planned using rigid pavement with a thick of base course is 30 cm and the surface layer of concrete is 20 cm. This layer will be used to coat the area serving AKAP and AKDP bus.Flexible pavement with a thickness of each layer is 35 cm for a foundation made of gravel sub-class A, 14 cm grade A layer of crushed stone as the foundation and the surface layer is 13 cm Laston MS 744 is used to coat the area of public transportation and angkudes. Pavement paving installed on any platform and access for pedestrians and sidewalk ceramics installed in the area of public service.Meanwhile, pavement paving installed on every platform and access for the pedestrian. Plan for the budget needed for the construction of the new terminal is Rp 28,987,398,500.00 includes costs of preparatory work, the main building terminal, construction of supporting facilities and infrastructure building.